2007
DOI: 10.1038/sj.bjc.6603570
|View full text |Cite
|
Sign up to set email alerts
|

A phase I/II study of irinotecan when added to 5-fluorouracil and leucovorin and pelvic radiation in locally advanced rectal cancer: a Colorectal Clinical Oncology Group Study

Abstract: The objective of this study was to evaluate the maximum tolerated dose (MTD) and recommended dose of irinotecan administered as a 5-day schedule synchronously with 5-fluorouracil (5FU), leucovorin (LV) and preoperative pelvic radiation (45 Gy) for primary borderline/unresectable, locally advanced rectal cancer. The study used escalating doses of intravenous irinotecan (6, 8, 10, 12, 14, 16, 18, and 20 mg m À2 ) administered on days 1 -5 and 29 -33 followed by low dose LV (20 mg m À2 ) and 5FU (350 mg m À2 ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(17 citation statements)
references
References 38 publications
0
16
1
Order By: Relevance
“…Furthermore, the resection rate achieved in this study is higher than that observed in studies using radiotherapy alone (range, 64 -75%) (Emami et al, 1982;Frykholm et al, 2001) or in some studies of CRT regimens (62 -95%) (de la Torre et al, 1999;Frykholm et al, 2001;Klautke et al, 2006;Glynne-Jones et al, 2007), and it is comparable to that cited in other reports of research with irinotecan (90 -100%) (Minsky et al, 1999;Mitchell et al, 2004;Klautke et al, 2005;Sebag-Montefiore et al, 2005). It is worth noting, that this current trial included only patients with T3/T4 cancers-that is patients with more advanced disease than those included in previously published studies.…”
Section: Discussioncontrasting
confidence: 47%
See 3 more Smart Citations
“…Furthermore, the resection rate achieved in this study is higher than that observed in studies using radiotherapy alone (range, 64 -75%) (Emami et al, 1982;Frykholm et al, 2001) or in some studies of CRT regimens (62 -95%) (de la Torre et al, 1999;Frykholm et al, 2001;Klautke et al, 2006;Glynne-Jones et al, 2007), and it is comparable to that cited in other reports of research with irinotecan (90 -100%) (Minsky et al, 1999;Mitchell et al, 2004;Klautke et al, 2005;Sebag-Montefiore et al, 2005). It is worth noting, that this current trial included only patients with T3/T4 cancers-that is patients with more advanced disease than those included in previously published studies.…”
Section: Discussioncontrasting
confidence: 47%
“…Considering CRM involvement, 81% of patients in this study who underwent TME surgery were classed as R 0 after surgery (CRM-negative). In studies that report data on the number of CRM-negative cases, results range from 61 -74% with radiotherapy (Emami et al, 1982;Frykholm et al, 2001) to 72 -89% with 5-FUbased protocols (de la Torre et al, 1999;Frykholm et al, 2001;Avallone et al, 2006;Klautke et al, 2006;Glynne-Jones et al, 2007) or 88 -89% when irinotecan is given as part of the CRT regimen (Klautke et al, 2005;Sebag-Montefiore et al, 2005). The addition of irinotecan to CRT regimens does not, therefore, seem to increase the high rate of CRM-negative surgery reported previously, but CRT certainly seems to be more successful than radiotherapy alone.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Irinotecan at 18 mg/m 2 was selected as the recommended dose for future studies. A pCR was observed in 24% patients and tumor downstaging in 41% of patients (Glynne-Jones et al, 2007). The above studies incorporating irinotecan with 5-FU and radiation appear to show promising results, as seen in the pCR rate and the number of patients who eventually had successful surgery.…”
Section: Irinotecan/5-fu Plus Radiotherapymentioning
confidence: 67%